2011
DOI: 10.1074/jbc.m110.198796
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Repair of Oxidized Base Damage in the Transcribed Genes of Mammalian Cells

Abstract: Preferential repair of bulky DNA adducts from the transcribed genes via nucleotide excision repair is well characterized in mammalian cells. However, definitive evidence is lacking for similar repair of oxidized bases, the major endogenous DNA lesions. Here we show that the oxidized base-specific human DNA glycosylase NEIL2 associates with RNA polymerase II and the transcriptional regulator heterogeneous nuclear ribonucleoprotein-U (hnRNP-U), both in vitro and in cells. NEIL2 immunocomplexes from cell extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
151
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 52 publications
6
151
1
Order By: Relevance
“…Previous studies (17)(18)(19)(20)(21)(22)(23)(24)(35)(36)(37) have demonstrated transcription-coupled nucleotide/base excision repairs. However, it remained unknown whether transcription-coupled DSB repair exists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (17)(18)(19)(20)(21)(22)(23)(24)(35)(36)(37) have demonstrated transcription-coupled nucleotide/base excision repairs. However, it remained unknown whether transcription-coupled DSB repair exists.…”
Section: Resultsmentioning
confidence: 99%
“…In TC-NER, recognition of the lesion is tied to RNA polymerase stalling at the DNA damage site and involves Rad26p in yeast or Cockayne syndrome group B protein (CSB) in humans (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Like TC-NER, base excision repair is also coupled to transcription (35)(36)(37). However, it is yet to be determined whether DSB repair is coupled to transcription.…”
mentioning
confidence: 99%
“…Contrary to the common perception that the repair of oxidatively damaged bases in DNA via the BER pathway involves only a few conserved repair proteins, a more complex picture of BER is now emerging in that BER comprises several alternative subpathways that utilize distinct sets of repair enzymes and other proteins (16,19,21,35,46). We have been exploring the role of noncanonical proteins in oxidized base repair and have characterized the proteins present in immunoprecipitates of early BER enzymes including DGs.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian expression plasmids for C-terminally FLAG-tagged NEIL1 were previously described (33,35). Log-phase HEK293 cells (in 6-cm plates) were transfected with 1 g of NEIL1-FLAG or the empty vector plasmid (19). After 24 h, the cells were trypsinized and plated in fresh medium containing Zeocin (100 g/ml) to select clones carrying stably integrated plasmid DNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation